2006
DOI: 10.1097/01.wnp.0000214596.69436.e0
|View full text |Cite
|
Sign up to set email alerts
|

Localizing Sites of Activation in Primary Visual Cortex Using Visual-Evoked Potentials and Functional Magnetic Resonance Imaging

Abstract: This study compared retinotopic map identification in primary visual cortex (V1) using: (i) functional magnetic resonance imaging (fMRI) and (ii) visual evoked potentials (VEPs) coupled with dipole source localization (DSL). A multielectrode array was used to record VEPs while subjects viewed a flickering dartboard pattern modulated by a 16-bit m-sequence. The stimulus preferentially activates V1. Using a common time function DSL algorithm, the primary source of each stimulus patch was found independent of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Using EEG alone, a resolution of about 3 degrees of visual angle can be obtained when individual MRIs are used to define the source space, and with a prior on where electrical signals are likely to originate (Im et al, 2007). Furthermore, by accurately mapping the likely current direction in a restricted source space around primary visual areas, it is possible to differentiate the activations in V1 and V2 (Ales et al, 2009;Baker et al, 2006). This way, it could be shown that V1 and V2 have comparable response latencies.…”
Section: Early Visual Responsesmentioning
confidence: 96%
See 1 more Smart Citation
“…Using EEG alone, a resolution of about 3 degrees of visual angle can be obtained when individual MRIs are used to define the source space, and with a prior on where electrical signals are likely to originate (Im et al, 2007). Furthermore, by accurately mapping the likely current direction in a restricted source space around primary visual areas, it is possible to differentiate the activations in V1 and V2 (Ales et al, 2009;Baker et al, 2006). This way, it could be shown that V1 and V2 have comparable response latencies.…”
Section: Early Visual Responsesmentioning
confidence: 96%
“…This assumes that the EEG scalp potentials result from one, or a few, cortical generators. With dipole source localization, striate cortex can be localized from the EEG scalp data (Di Russo et al, 2002;Ikeda et al, 1998) in good agreement with fMRI data (Baker et al, 2006). But even though the scalp potentials of the first evoked EEG component, the C1 at around 80-90 ms, are consistent with a single cortical dipole (Jeffreys and Axford, 1972), the underlying source activity is known to be more complex.…”
Section: Introductionmentioning
confidence: 95%
“…5 More recently Sharon and colleagues compared source identification using EEG and MEG separately as well as combined. 6 Localization perfomance based on EEG data was similar to our earlier findings.…”
Section: Combining Eeg and Meg For Source Identificationmentioning
confidence: 99%
“…We have previously shown that by assuming a common time function for all cortical sources that correspond to a ring of stimulus patch within a visual area, an accurate estimation of the time function is possible (see Appendix 3 for details.). 5,13 Here we apply additional cortical constraints given by the MRI/fMRI results. The voltages (V) recorded on electrodes (e) for a ring of stimulus patches (p), or hemi ring of patches for a single hemisphere is:…”
Section: Our New Algorithm For Extracting V1 and V2 Temporal Responsesmentioning
confidence: 99%
See 1 more Smart Citation